Concomitant administration of a fully liquid ready-to-use DTaP-IPV-HB-PRP-T hexavalent vaccine with a meningococcal ACWY conjugate vaccine in toddlers. Issue 52 (18th December 2018) - Vesikari, Timo; Borrow, Ray; Da Costa, Xavier; Thomas, Stéphane; Eymin, Cécile; Boisnard, Florence; Lockhart, Stephen
Highlights: Immunogenicity findings support DTaP-IPV-HB-PRP-T and MenACWY-TT co-administration. Safety findings support DTaP-IPV-HB-PRP-T and MenACWY-TT co-administration. MenC-TT use during infancy does not preclude MenACWY-TT use for booster vaccination. Abstract: Invasive meningococcal disease caused by Neisseria meningitidis is a life-threatening disease. Several countries now include meningococcal serogroup C (MenC) conjugate and, more recently, a meningococcal serogroup ACWY conjugate (MenACWY) vaccination in their national immunization schedules. DTaP-IPV-HB-PRP-T is a hexavalent vaccine that provides protection against six diseases. The phase III, open-label, randomised, multicentre study enrolled healthy toddlers who received the DTaP-IPV-HB-PRP-T vaccine (at 2, 3 and 4 months) with or without a MenC vaccine (at 2 and 4 months) in the primary series study. At 12 months of age, 312 toddlers were randomised to receive DTaP-IPV-HB-PRP-T co-administered with MenACWY-TT vaccine (Group A; n = 104); DTaP-IPV-HB-PRP-T vaccine alone (Group B; n = 105); or MenACWY-TT vaccine alone (Group C; n = 103). At 12 months of age, there were no notable differences in terms of antibody persistence for any DTaP-IPV-HB-PRP-T vaccine antigen, whether MenC-TT conjugate vaccine was co-administered or not during the primary series. Following booster vaccination, immune responses to DTaP-IPV-HB-PRP-T and MenACWY-TT vaccines were not affected by co-administration. One month after vaccination, the immune responses elicited by both vaccines were high, whether administered concomitantly or separately. The administration of MenC vaccine during infancy did not preclude the use of a MenACWY-TT vaccine for booster vaccination. Even though the reactogenicity after co-administration was somewhat higher, the results of this study support the concomitant administration of the DTaP-IPV-HB-PRP-T vaccine with a MenACWY-TT conjugate vaccine when given from 12 months of age. The clinical trial registration numbers are:clinicaltrial.gov : NCT01839175; EudraCT: 2012-005547-24.